The Impact of Employee Satisfaction, Organizational Commitment, Job Performance and Teamwork as the Success Factors in FedEx: A Study of FedExâ€™s Employees in Malaysia - Koh Jhee Qing; Daisy Mui Hung Kee; Joel Chen Tai Soon; Chin Kah Hui; Châ€™ng Kelvin; Abishek Singh; Obaja Elka Kurniawan; Aisha Bader Alotaibi; Rudresh Pandey; Majdi Anwar Quttainah; Liem Gai Sin (AIBPM Publisher, 2020)
In 1971, FedEx was founded as Federal Express Corporation, by Frederick W. Smith. In the world of supply chain services, FedEx is one of the most trusted and respected brands. The main goal of FedEx is to make sure that FedEx is their customers' first choice, by delivering world-class customer experience. FedEx ensures that they deliver world-class customer experience to their customers so that their loyalty towards FedEx will grow and they will not risk trying another carrier service. FedEx takes care of its people first, believing they will then take care of its customers. For this reason, FedEx top leaders commit the â€œPeople Firstâ€ philosophy.